Unfiltered Market Access and Liquidity: Evidence from the SEC Rule 15c3-5 - Chakrabarty, Bidisha; Jain, Pankaj K.; Shkilko, Andriy; Sokolov, Konstantin (Management Science, 2021)
In November 2011, the U.S. Securities and Exchange Commission implemented the final provision of Rule 15c3-5 curbing unfiltered market access. The provision mandated that brokers verify their clients’ order flow for compliance with credit and capital thresholds before routing to market centers. We find that the new checks introduce latency to order flow and force some latency-sensitive strategies out of the market. As a result, liquidity providers are better able to revise their quotes in response to new information, adverse selection declines, and liquidity improves. Consistent with the notion that the market for liquidity provision is competitive, our results show that the benefit of lower adverse selection is transferred entirely to liquidity demanders in the form of lower trading costs. This paper was accepted by Karl Diether, finance.